(untitled) (African Journal for Industrial and Applied Mathematics, 2025)
In this short note, we establish the Existence and stability of solutions of an abstract semilinear differential equation governed by the so-called deformable derivative. We achieve our results using Banach’s contraction principle, the Laplace transform, and the Gronwall inequality. These results are new in the context of fractional differential equations.